2010
DOI: 10.1007/s00432-010-0812-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis of a highly metastatic variant of human breast cancer cells using two-dimensional differential gel electrophoresis

Abstract: Distant metastasis represents the major lethal cause of breast cancer. To understand the molecular mechanisms of breast cancer metastasis and identify markers with metastatic potential, we established a highly metastatic variant of parental MDA-MB-231 cells (MDA-MB-231HM). Using two-dimensional electrophoresis (2-DE), we performed a proteomic comparison of the two kinds of cells. As much as 51 protein spots were differentially expressed between the selected variant and its parental counterpart in at least 3 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…It is frequently downregulated in breast, colon (Shields et al, 2002;Wulfkuhle et al, 2002) and prostate cancers (Yang et al, 2007), where a tumor suppressor function has been proposed. In colorectal cancer, negative TAGLN expression has further been reported to be an independent prognostic indicator for shorter patient's survival (Zhao et al, 2009), whereas a role in impeding metastasis was suggested in breast carcinoma (Xu et al, 2010). TAGLN also acts to suppress the expression of metallo-matrix proteinase MMP9, which is an important enzyme involved in the tissue remodeling during cancer cells invasion into the surrounding tissues (Nair et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently downregulated in breast, colon (Shields et al, 2002;Wulfkuhle et al, 2002) and prostate cancers (Yang et al, 2007), where a tumor suppressor function has been proposed. In colorectal cancer, negative TAGLN expression has further been reported to be an independent prognostic indicator for shorter patient's survival (Zhao et al, 2009), whereas a role in impeding metastasis was suggested in breast carcinoma (Xu et al, 2010). TAGLN also acts to suppress the expression of metallo-matrix proteinase MMP9, which is an important enzyme involved in the tissue remodeling during cancer cells invasion into the surrounding tissues (Nair et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CapG overexpression has been reported in several cancer types, such as breast carcinoma (Kang et al, 2010;Xu et al, 2010), ovarian adenocarcinoma (Partheen et al, 2008), oral carcinoma (Nomura et al, 2008), pancreatic cancer (Thompson et al, 2007a,b), and ocular melanoma (Van Ginkel et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study of pancreatic ductal adenocarcinomas previously showed that high CapG expression was correlated with increased tumor size (Thompson et al, 2007a,b). Some researchers have reported that RNAi knockdown of CapG in human cancer cells, such as breast and pancreatic cancer cells can significantly reduce the invasion and motility of cancer cells and cell aggression (Dahl et al, 2005;Thompson et al, 2007a,b;Kang et al, 2010;Xu et al, 2010). CapG is considered to be a tumor promoter and can modulate invasive properties of cells during tumorigenesis (Veerle et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NDRG1 protein expression has been described to be present in normal brain or brain tumor tissue [11] as well as being an important gene that is playing an active role in the regulation of a broad spectrum of human cancer diseases like human gastric cancer, squamous cell carcinomas, breast cancer, human hepatocellular carcinoma, brain tumors and leukemia [12][13][14][15][16][17][18][19][20][21][22] . NDRG1 was suggested to be a prognostic marker for hypoxic regions within a tumor mass because of its stability as a protein [23][24][25] and because it is highly expressed in malignant tumor tissues compared to normal tissue of the same origin [26] .…”
Section: Discussionmentioning
confidence: 99%
“…g/mL streptomycin, and 100 units/mL penicillin). The pSUPER-NDRG1 vectors were designed as mentioned before [10][11][12][13][14][15][16][17] . To establish pSUPER-NDRG1, two sequences were selected from the human NDRG1 cDNA (5'-GCATTATTGGCAT-GGGAAC-3' (positions 398-416) and 5'-ATGCAGAG-TAACGTGGAAG-3' (positions 601 to 619), relative to the start codon).…”
Section: Preparation Of Nuclear Extracts Whole-cell Lysates and Immumentioning
confidence: 99%